2002
DOI: 10.1038/sj.onc.1205584
|View full text |Cite
|
Sign up to set email alerts
|

p53 induces the expression of its antagonist p73ΔN, establishing an autoregulatory feedback loop

Abstract: The p53 tumor suppressor protein activates transcription and induces cell death. A close homologue of p53, termed p73, is expressed in transactivating (TA) forms that induce growth arrest and apoptosis much like p53. However, the p73 gene contains a second promoter, giving rise to the expression of p73DN, a species of p73 proteins that lack the N-terminal transactivation domain. We show here that the expression of p73DN is induced by p53 on the mRNA and protein level. The promoter that regulates p73DN expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
134
3
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 70 publications
15
134
3
4
Order By: Relevance
“…We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a). Such a dominant-negative function of DNp73 has also been observed in this study with respect to hTERT regulation.…”
Section: Regulation Of Htert By P73 M Beitzinger Et Alsupporting
confidence: 80%
See 1 more Smart Citation
“…We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a). Such a dominant-negative function of DNp73 has also been observed in this study with respect to hTERT regulation.…”
Section: Regulation Of Htert By P73 M Beitzinger Et Alsupporting
confidence: 80%
“…In contrast to downregulation of hTERT by differentiation or proapoptotic stress signals, hTERT is typically activated in immortal cells and established tumors . We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a).…”
Section: Regulation Of Htert By P73 M Beitzinger Et Almentioning
confidence: 99%
“…Wtp53 tumours had higher TAp73 levels than mutant p53 tumours, a finding that is not easily explained (wtp53 has been shown to transactivate ΔNp73 from the P2 promoter but not the P1 promoter 22 ). On the other hand, despite the drop in ΔNp73 mRNA levels in stage III, immunoblot analysis revealed that the total levels of ΔNp73 protein were comparable between the two stages.…”
Section: Discussionmentioning
confidence: 89%
“…Promoter competition by DNp73 at TAp73/p53 response elements is another transdominant mechanism. 11,12 Highly prevalent tumor-specific upregulation of DNp73 has already been found in several studies. 8,9,[16][17][18][19] For example, we reported that DNp73/DN 0 p73 transcripts are overexpressed in 73% of 37 gynecological cancers and DN 0 p73 transcripts are upregulated in 87% of 100 ovarian cancers.…”
mentioning
confidence: 83%
“…[9][10][11][12] They act as powerful inhibitors of p53 and TAp73 since they retain their DNA-binding and tetramerization competence. [7][8][9]11,13,14 In cultured cells, DNp73 abrogates the suppressive activity of p53 and TAp73 and inactivates their ability to induce apoptosis and cell cycle arrest.…”
mentioning
confidence: 99%